1996
DOI: 10.1055/s-2008-1058651
|View full text |Cite
|
Sign up to set email alerts
|

Residual and Recurrent Acoustic Neuroma in Hearing Preservation Procedures: Neuroradiologic and Surgical Findings

Abstract: Hearing preservation procedures in acoustic neuroma surgery entail a risk of recurrent tumor either from the preserved cochlear nerve (tumor cell remains or late degeneration) or from tumor remnants left in the lateral end of the internal auditory canal. There is disagreement about the frequency of such tumor remnants, and the diagnostic modalities are not precise. Magnetic resonance imaging with gadolinium-DTPA enhancement is effective in diagnosing a primary case, but may not be so clear for small residual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Cerullo, et al, [2] noted a 10% recurrence rate by 10 years following resection. Mazzoni, et al, [19] reported their series of more than 100 patients in whom they attempted hearing preservation; the overall tumor recurrence rate was 8.1%. Post, et al, [24] found that four (7%) of 56 patients underwent an incomplete resection in their attempted hearing-preservation series and that three developed regrowth within 3 years.…”
Section: Tumor Resection or Radiosurgery?mentioning
confidence: 97%
“…Cerullo, et al, [2] noted a 10% recurrence rate by 10 years following resection. Mazzoni, et al, [19] reported their series of more than 100 patients in whom they attempted hearing preservation; the overall tumor recurrence rate was 8.1%. Post, et al, [24] found that four (7%) of 56 patients underwent an incomplete resection in their attempted hearing-preservation series and that three developed regrowth within 3 years.…”
Section: Tumor Resection or Radiosurgery?mentioning
confidence: 97%
“…Clinical studies have confirmed that of the 3 commonly used surgical approaches, the retrosigmoid route has the highest risk that unintentional tumor will be left behind, especially in the lateral one-half to one-third of the IAC. 15,23 Furthermore, in contrast to small remnant disease left along the facial nerve in the midcistern, tumor at the fundus is well vascularized, and therefore, it may be more apt to demonstrate continued growth and clinically significant recurrence. 6 Several studies have examined postoperative MR imaging enhancement patterns following retrosigmoid VS resection, but all studies to date have not investigated the location of enhancement in relation to the extent of preoperative tumor.…”
Section: Discussionmentioning
confidence: 99%
“…While the retrosigmoid approach provides excellent medial exposure, the lateral one-third of the IAC cannot be routinely visualized if the inner ear is to be preserved, leaving the fundus particularly vulnerable to recurrence. 5,15,17,23 Several studies have found that, following GTR, the presence of nodular enhancement within the tumor bed predicts a high likelihood for future recurrence. 4,15,16,28 Over the past 10 years we have observed a number of patients in whom intense nodular enhancement was documented at the fundus of the IAC lateral to the preoperative radiological tumor margin following retrosigmoid GTR.…”
mentioning
confidence: 99%
“…A report by Cerullo et al [17, Class III] noted a 10% recurrence rate by 10 years following resection. Mazzoni et al [18] reported their series of over 100 patients with attempted hearing preservation. The overall tumor recurrence rate was 8.1%.…”
Section: Tumor Resection or Radiosurgery?mentioning
confidence: 98%